Collaborative Product and Service Life Cycle Management for a Sustainable World - Curran, Richard (Springer-Verlag London, 2017)
Current computer-aided layout design systems only support layout state generation, which is not ideal for engineering layout design based on distributed knowledge and intelligent environment. This paper proposes a system framework to enable distributed engineering layout design in service-oriented architecture. A federated layout design system based on Service-ORiented Computing EnviRonment (SORCER) implements the framework. In order to supply design services to users, distributed design resources and design tools can be wrapped as SORCER service providers. And the users should be wrapped as service requestors so that they can join in the federated layout design system. A layout design interface protocol is developed to define standardized design services for whole layout process. The protocol content include standard layout components and containers representation, design parameter, layout state representation, design constrain representation and human-computer interaction command etc. Data interoperability between services is enhanced by design context communication. In order to be free loaded and used in the federated layout design system, each service needs to implements the interface protocol strictly. This system aims to enable asynchronous distributed collaborative design with ease of alternative design services, reduced design cycles, and improved layout resolution quality.